(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This study is based on descriptive and analytical research to deal with teacher competencies. The study has defined the factors influencing the teaching competency of any teacher. The main objectives of the study were to find out the factors affecting teacher competencies and to study the studies related to this concept.